Importing and exporting gods?: On the flow of deities between Egypt and its neighboring countries - Quack, Joachim Friedrich (The dynamics of transculturality, 2015)
This is a case study concerning the interaction between Ancient Egypt and its neighbors, as far as deities are involved. The chapter shall illustrate how several quite different attitudes can be perceived under different political and social conditions. In the earliest periods for which we have written sources available, we can already demonstrate that deities of foreign origin were known in Egypt and received some attention--but at the same time that deities whose origins are likely to be Egyptian could be stylized as lords of foreign regions. These Egyptian deities could actually be taken up by the locals if they wrote in Egyptian language, at least in places with particularly strong ties to Egypt. Foreign deities could also be taken up by Egyptians as a form of “learned borrowing,” especially for magical purposes. A substantial veneration of foreign deities was introduced by migrants, although the details vary considerably between different ethnicities, with some establishing substantial cults of their traditional gods and others almost abandoning them. Egyptian gods had a considerable impact in foreign countries as images, but their names and the details of their mythology were rarely taken up in detail before the Hellenistic period. Finally, there are a few real as well as fictional attestations that specific powerful, divine statues could be lent to other countries for a limited time. Taken together, these different facets serve as examples of the various reactions under different socio-political conditions in an early form of globalization.
First online: 10 October 2014
Gesehen am 26.05.2020